Identifying insertion mutations by whole-genome sequencing - Harold E. Smith (BioTechniques)
Insertion mutagenesis via mobile genetic element is a common technique for the analysis of gene function in model organisms. Next-generation sequencing offers an attractive approach for localizing the site of insertion, but alignment-based mapping of mobile genetic elements is challenging. A computational method for identifying insertion sites is reported herein. The technique was validated by mapping transposons in both bacterial and nematode species. The approach should be extensible to other systems that employ mobile genetic elements to generate mutations.